ChemInform Abstract: Catalyst Design in the Alkane C‐H Bond Functionalization of Alkanes by Carbene Insertion with TpxM Complexes (Tpx = Hydrotrispyrazolylborate Ligand; M = Cu, Ag). Issue 43 (October 2015) - Caballero, Ana; Perez, Pedro J.
Abstract Review: 52 refs.